Synthesis, modification and application of fish skin gelatin-based hydrogel as sustainable and versatile bioresource of antidiabetic peptide - Munawaroh, Heli Siti Halimatul (2023)
Gelatin hydrogel is widely employed in various fields, however, commercially available gelatin hydrogels are mostly derived from mammalian which has many disadvantages due to the supply and ethical issues. In this study, the properties of hydrogels from fish-derived collagen fabricated with varying Glutaraldehyde (GA) determined. The antidiabetic properties of salmon gelatin (SG) and tilapia gelatin (TG) was also evaluated against α-glucosidase. Glutaraldehyde-crosslinked salmon gelatin and tilapia gelatin were used, and compared with different concentrations of GA by 0.05 %, 0.1 %, and 0.15 %. Water absorbency, swelling, porosity, pore size and water retention of the hydrogels were dependent on the degree of crosslinking. The synthesis of hydrogels was confirmed by FTIR study. Scanning electron microscope (SEM) observation showed that all hydrogels have a porous structure with irregular shapes and heterogeneous morphology. Performance tests showed that gelatin-GA 0.05 % mixture had the best performance. Antidiabetic bioactivity in vitro and in silico tests showed that the active peptides of SG and TG showed a high binding affinity to α-glucosidase enzyme. In conclusion, SG and TG cross-linked GA 0.05 % have the potential as an antidiabetic agent and as a useful option over mammalian-derived gelatin.